2012
DOI: 10.1037/a0026326
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent turning points: The association between meaning-making and psychological well-being.

Abstract: Research findings indicate that the ability to create meaning out of turning points (i.e., significant life experiences) is related to psychological well-being. It is not clear, however, whether individuals who report meaning-making and higher well-being are better adjusted prior to the experience of their turning point event. This study examined whether meaning-making and timing of turning points would be associated with higher scores on well-being. Participants were 418 Grade 12 students (209 of whom reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
79
3
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(88 citation statements)
references
References 44 publications
(85 reference statements)
4
79
3
2
Order By: Relevance
“…Interpreting and integrating disruptive life events is potentially beneficial for wellbeing [Pals, 2006;Park, 2010]. More specifically, among 12th-graders who reported having experienced a turning point, those who included learning a lesson or an insight in their turning point narrative reported higher well-being than those whose narratives did not include meaning making, even after controlling for their earlier well-being [Tavernier & Willoughby, 2012]. In the lifespan sample of the Frankfurt longitudinal study MainLife, having experienced changes in life circumstances in the past four years led to a lower sense of self-continuity.…”
Section: Autobiographical Reasoning and Well-being Across Adolescencementioning
confidence: 97%
“…Interpreting and integrating disruptive life events is potentially beneficial for wellbeing [Pals, 2006;Park, 2010]. More specifically, among 12th-graders who reported having experienced a turning point, those who included learning a lesson or an insight in their turning point narrative reported higher well-being than those whose narratives did not include meaning making, even after controlling for their earlier well-being [Tavernier & Willoughby, 2012]. In the lifespan sample of the Frankfurt longitudinal study MainLife, having experienced changes in life circumstances in the past four years led to a lower sense of self-continuity.…”
Section: Autobiographical Reasoning and Well-being Across Adolescencementioning
confidence: 97%
“…These meaningmaking processes have also been found to be important in fostering well-being across time. For example, Tavernier & Willoughby (2012) found that although adolescents' well-being prior to a stressful event was unrelated to post-stress meaning-making, this meaning-making was related to increases in well-being over time. It is therefore not an individual's prior level of adjustment that seems to be important, but individual differences in specific personality traits that may play an important role in facilitating the meaning making process.…”
Section: Turning Points and Gaining Wisdommentioning
confidence: 99%
“…This approach may facilitate an appraisal-centred approach to stress (Lazarus, 1993) as well as meaning-making attempts (Park, 2010;Park & Folkman, 1997), all of which may ultimately facilitate interviewees' perception of meaningfulness. The latter is an important aspect of PWB (Auhagen, 2000;Debats, 1999;Debats et al, 1995;Frankl, 1959Frankl, / 1992Maddi, 1967;Park & Gutierrez, 2013;Skaggs & Barron, 2006;Tavernier & Willoughby, 2012;Zika & Chamberlain, 1992). Promoting interviewees' PWB in an investigative interview context is in line with the ideology of TJ (Slobogin, 1995;Stolle et al, 2000;Wexler, 1996a).…”
Section: Participants' Psychological Well-being In Terms Of Socmentioning
confidence: 84%
“…Second, and related to interviewees' narration, are opportunities for the interviewees to reappraise the significance of the experienced events, a strategy that is in line with meaning-making attempts and meaning made (Park, 2010;Park & Folkman, 1997). Several studies (Pennebaker et al, 1988;Petrie et al, 1998;Richards et al, 2000) have suggested a relation between individuals' disclosure of traumatic events and reduced stress, and that the formation of a narrative is critical and a predictor of good mental health (Pennebaker & Seagal, 1999), which, in turn, is associated with PWB through the meaning-making process (Park & Gutierrez, 2013;Tavernier & Willoughby, 2012). Moreover, with the above in mind, a previous study by Holmberg and Madsen (2014) found that interviewees subjected to a non-rapport condition, in contrast to those interviewed with a humanitarian rapport style, reported less information altogether, particularly less peripheral information.…”
Section: Participants' Psychological Well-being In Terms Of Anxietymentioning
confidence: 96%
See 1 more Smart Citation